2021
DOI: 10.1016/j.wem.2021.03.006
|View full text |Cite
|
Sign up to set email alerts
|

The Usefulness of Platelet Distribution Width and Platelet Distribution Width to Lymphocyte Ratio in Predicting Severity and Outcomes in Patients with Snakebite

Abstract: Introduction-Tissue damage, inflammatory response, and hematologic abnormalities may occur in snakebite envenomation. This study aimed to evaluate the predictive ability of platelet distribution width (PDW) and platelet distribution width to lymphocyte ratio (PDWLR) in the severity and outcome of envenomation in patients with snakebites in the emergency department (ED).Methods-All adult patients admitted to the ED after a snakebite were retrospectively evaluated. Patients were classified according to the sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…One study in Sri Lanka showed that hemostatic dysfunction developed in 6% of patients after hump-nosed viper bites [ 18 ]. Another study in Turkey detected hematological abnormalities in 15% of the patients [ 19 ]. Coagulation disorder was detected in 25% of our patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study in Sri Lanka showed that hemostatic dysfunction developed in 6% of patients after hump-nosed viper bites [ 18 ]. Another study in Turkey detected hematological abnormalities in 15% of the patients [ 19 ]. Coagulation disorder was detected in 25% of our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Çelik et al examined scorpion stings in children and showed that increased platelet and PCT values were predictive of serious clinical conditions [ 26 ]. In another study, an increased PDW and PDW to lymphocyte ratio showed a poor prognosis in snakebites [ 19 ]. In our study, however, PCT was found to be lower in the group with serious complications and was predictive of a poor outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory analysis was also an effective tool to predict PSCS [ 8 , 9 ]. In a study [ 9 ], 6.6% (9/136) patients developed PSCS and the authors found a significant increase in the white blood cell (WBC) count, segment form, aspartate aminotransferase level, and alanine aminotransferase level in the PSCS group.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, PDWLR has been assessed as a tool to predict the severity and risk of death in patients with snake bites, as well as cardiovascular disease risk [15,16].…”
Section: Auc -Area Under the Curve Mpvlr -Mean Platelet Volume To Lym...mentioning
confidence: 99%
“…The platelet distribution width to lymphocyte ratio (PDWLR), which is easily calculated by dividing the PDW by lymphocyte count, has emerged as a predictor of cardiovascular risk and severity of snakes bites [15,16]. In the literature, several studies have assessed the MPV and PDW in relation to SLE disease activity [7,[17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%